Frontispiece: Organic semiconducting nanomaterials‐assisted phototheranostics in near‐infrared‐II biological window (View 1/2021). Issue 1 (6th February 2021) - Yin, Chao; Lu, Xiaomei; Fan, Quli; Huang, Wei
Abstract : In article number 20200070, Quli Fan and his colleagues have displayed that several "spheres" with different characteristics float above the sea that dissolved lots of organic semiconducting molecules highlighted by the light beam from the lighthouse, symbolizing that nanomaterials constructed from organic semiconducting molecules have the versatility in biomedical diagnostics (fluorescence imaging and photoacoustic imaging) and therapy (photothermal therapy, chemotherapy, and surgery) assisted by light irradiation.